Analysis and design of snubber circuit for Z‐source inverter applications. Issue 5 (1st April 2016) - Dong, Shuai; Zhang, Qianfan; Cheng, Shukang
Abstract : The Z‐source inverter (ZSI) is a topology with many advantages for power electronics interfaces. Shoot‐through states are utilised to boost the DC‐link voltage. This study shows that traditional C, RC, RCD, and RCD clamp snubber circuits are not suitable for ZSI. When these snubber circuits are used for ZSI, there will be a distortion in the DC‐link voltage, and this voltage will be higher than that without the snubber circuits. The shoot‐through state causes larger energy losses, which greatly lowers the efficiency of ZSI. This study presents an improved RCD snubber circuit for ZSI applications. This design reduces the voltage distortion and energy losses. In addition, the theoretical analysis and design guidelines for snubber circuits of ZSI are confirmed by computer simulation and experimental verification.